Experimental studies on effect of heat transfer with Cuo-H2O nanofluid on flat plate Heat Pipe. (2017) - Mohanraj, C.; Dineshkumar, R.; Murugan, G.
Abstract: The present study is focused on heat transfer performance of a flat plate heat pipe with Nano fluids. A flat plate heat pipe is successful heat transfer device for space, energy technology and electronic cooling application. The present experimental investigation was carried out for flat plate heat pipe with CuO Nano fluid the flat plate heat pipe was fabricated by using copper which has good heat transfer characteristics. The Nano fluid was prepared with CuO and DI water. This process was carried out by ultrasonic vibrator. The experimentation was carried out for two different working fluid, that was DI water and (DI water and Nano particle). The heat release rate was observed by data logger with different heat inputs. Finally both results were compared and heat pipe with Nano fluid was given good heat release rate than DI water. The plot was drawn for both the working fluids.